The surjective map sends $x$ to $1$ btw, and the injective map is inclusion. The case $n=0$ I've shown too. I tried to mimick my proof for the special case $R=\mathbb Z_2$ where I considered I short exact sequence, which in the general case would be
$$
0\to R(1-x)\to\frac{R[x]}{(x^2-1)}\to R\to 0.
$$
By the long exact sequence for $\text{Ext}$ it would suffice to know what $\text{Ext}(R(1-x),R)$ is. I could also invoke the isomorphism $\frac{R[x]}{(x^2-1)}\cong\frac{R[y]}{(y(y-1))}$ in which case the kernel would be $R(2-y)$, which might be easier to work with. At this point I'm stuck thoug…